Students’ Creative Writings Mirroring the Social Reality - Paneru, Pragya (Technium Social Sciences Journal, 2023)
This article analyses a total of forty-six students’ writings from Grade 11 to master’s level published in one of the college’s annual magazines. Among them 24 are females and 22 are males. This research uses a qualitative content analysis method to analyze the students’ writings under various topics and genres to unearth their concerns. Although there are multiple studies on students’ creative writings focusing on the technical and gender aspects, only a few studies focus on the issues reflected in their contents. This research believes that students’ creative writings are significant as they give information about the issues, interests, and concerns from students’ perspectives. The students’ writings also reflect their concerns and awareness of students regarding various social issues in their writings. The findings from this study revealed that students are concerned about multiple social and political issues in Nepal such as poverty, political corruption, cultural issues, gender discrimination, caste discrimination, and women issues. Moreover, life is a dominant theme in both male and female writings and they are concerned about their life, future goals, and responsibility toward their parents. Some shared themes are the challenges of staying away from parents for study purposes, caste discrimination, gender discrimination, poverty, child labor, and women-related issues. Females have written personalized writings with varieties of issues and dark themes than males and the themes in their writings suggest their struggle in a patriarchal society, social restrictions, gender discrimination, and women violence against males’ writings on general themes such as loss of human values, loss of culture, and struggle of orphaned children.